2020
DOI: 10.2196/19364
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Educational Control Group Mobile App for Meditation Interventions: Single-Group Feasibility Trial

Abstract: Background Smartphone ownership is becoming ubiquitous among US adults, making the delivery of health interventions via a mobile app (ie, mobile health [mHealth]) attractive to many researchers and clinicians. Meditation interventions have become popular and have been delivered to study participants via mobile apps to improve a range of health outcomes in both healthy adults and those with chronic diseases. However, these meditation mHealth interventions have been limited by a lack of high-quality … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 28 publications
0
10
0
8
Order By: Relevance
“…Regarding the data sources, 54% of the selected studies are found in Pubmed (n=6) (26)(27)(29)(30)33,35) , and 46% in grey literature databases -Open Thesis and Dissertations (n=4) (28,(31)(32)34) and the Catalog of Theses and Dissertations (n=1) (36) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the data sources, 54% of the selected studies are found in Pubmed (n=6) (26)(27)(29)(30)33,35) , and 46% in grey literature databases -Open Thesis and Dissertations (n=4) (28,(31)(32)34) and the Catalog of Theses and Dissertations (n=1) (36) .…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 portrays the studied outcomes related to the use of podcasts, evaluated in the analyzed studies (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) .…”
Section: Resultsmentioning
confidence: 99%
“…Although we included a wait-list control group to control self-selection and the inevitable changes that occur during PA school but not attributable to the intervention, future studies should include an active control condition. Although this has been challenging in studies of app-delivered mindfulness to date, recent work has advanced in this area toward developing smartphone apps that can be used as active comparators (eg, Huberty et al [ 60 ]).…”
Section: Discussionmentioning
confidence: 99%
“…For example, we replaced “overly negative” or “boring” content with more uplifting stories or engaging podcasts. The app has successfully been used as a control in multiple previous studies testing app-based meditation interventions [ 53 , 54 ].…”
Section: Methodsmentioning
confidence: 99%